Synergy of Golden Snail Local Microorganism (LMO) and Seed Age in Optimizing Rice Seed Germination - Zainal Abidin Zainal; mujibu Rahman; Moch. Bintoro; Suwardi; Rusmini; La Mudi; Yuanita; Roby; Daryono; Faradilla; F. Silvi Dwi Mentari (Jurusan Pertanian Politeknik Pertanian Negeri Samarinda Kampus Sei Keledang Jalan Samratulangi, Kotak Pos 192 Samarinda 75123, 2024)
This research aims to synergize local microorganisms (LMO) of golden snails (Pomacea canaliculata) and seed age in optimizing rice seed germination (Oryza sativa L.). Golden snail LMO, which is rich in organic nutrients and beneficial microorganisms, has the potential to improve seed quality and viability. The study used a factorial randomized block design (RBD) with two factors: golden snail LMO concentration (Control, 20 ml/L water, 40 ml/L water) and seedling age (7 days, 11 days, and 15 days after sowing). The variables observed included seed germination, simultaneity grows and growth speed. The results showed that the golden snail LMO concentration of 20 ml/L and seed age of 11 days after sowing gave the highest results for the observed variables, namely seed germination and growth speed while the interaction between golden snail LMO concentration mas 40 ml/L and seed age of 15 days after sowing gave the highest results for the variable observing growth synchrony. The combination of the two factors showed a positive interaction that supported the germination process effectively. This study concludes that the use of golden snail LMO and selecting the right seed age can be an ecological and efficient approach to increasing rice seed productivity, supporting sustainable agriculture.